The Effectiveness of Acceptance and Commitment Therapy on Marital Inhibition and Emotional Intimacy among Women in Second Marriages - Abedi Firouzjaei , Fatemeh; Abdollahizade, Mina Sadat; Armoon , Azadeh; Karimi , Sohila; Ahmadimoghadam, Maryam (Applied Family Therapy Journal (AFTJ), 2026)
Objective: The present study aimed to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on marital inhibition and emotional intimacy among women in second marriages.Methods and Materials: This study employed a quasi-experimental method using a pretest-posttest design with a control group. The statistical population consisted of women in second marriages who referred to counseling centers in Tehran in 2026. Using convenience sampling, 28 participants were selected and randomly assigned into experimental (n = 14) and control (n = 14) groups. Data were collected using the Marital Inhibition Questionnaire and the Emotional Intimacy Questionnaire. The experimental group participated in eight weekly 90-minute sessions of Acceptance and Commitment Therapy, whereas the control group received no intervention. Data were analyzed using analysis of covariance (ANCOVA) in IBM SPSS Statistics version 27 at a significance level of 0.05.Findings: The findings indicated that Acceptance and Commitment Therapy significantly reduced marital inhibition and increased emotional intimacy among women in second marriages. The results of covariance analysis for marital inhibition demonstrated a significant difference between the experimental and control groups in the posttest phase (F = 9.412, effect size = 0.148). In addition, the covariance analysis results for emotional intimacy revealed a significant difference between the two groups following the intervention (F = 13.845, effect size = 0.193). The posttest mean scores showed that marital inhibition decreased and emotional intimacy increased in the experimental group compared with the control group.Conclusion: Based on the findings, Acceptance and Commitment Therapy was effective in improving emotional intimacy and reducing marital inhibition among women in second marriages. By increasing psychological flexibility, emotional acceptance, and adaptive interpersonal functioning, ACT may help remarried women establish healthier emotional relationships and reduce maladaptive controlling behaviors within marital interactions.